2012
DOI: 10.1016/j.healthplace.2012.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Do obesity-promoting food environments cluster around socially disadvantaged schools in Glasgow, Scotland?

Abstract: Increase in the consumption of food and drinks outside the home by adolescents and young people and associations with rising levels of obesity is a significant concern worldwide and it has been suggested that the food environment around schools may be a contributory factor. As few studies have explored this issue in a UK setting, we examined whether different types of food outlets are clustered around public secondary schools in Glasgow, and whether this pattern differed by social disadvantage. We found eviden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
0
3

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 23 publications
4
46
0
3
Order By: Relevance
“…28 Previous studies do not make a distinction between convenience stores and small grocery stores, which are neighborhood stores with a small selection of healthy food options. [8][9][10]17,29,30 As a result, these studies offer little insight into the potential of upgrading these neighborhood stores to improve their healthy food offerings. Unlike previous research, [8][9][10]17,29,30 we did not find a significant association between proximity to convenience stores and students' weight status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 Previous studies do not make a distinction between convenience stores and small grocery stores, which are neighborhood stores with a small selection of healthy food options. [8][9][10]17,29,30 As a result, these studies offer little insight into the potential of upgrading these neighborhood stores to improve their healthy food offerings. Unlike previous research, [8][9][10]17,29,30 we did not find a significant association between proximity to convenience stores and students' weight status.…”
Section: Discussionmentioning
confidence: 99%
“…Also, unlike most previous work, we incorporated neighborhood factors [8][9][10]18,19,[29][30][31]33 in our model. Third, the study used professionally measured student height and weight data, rather than self-reported survey data.…”
Section: Discussionmentioning
confidence: 99%
“…Buck et al 13 did not find a significant number of fast food restaurants near elementary schools, which are frequented by younger students. However, FO related results are contradictory, with studies finding more 37 or fewer 29,30 establishments near high schools than elementary schools.…”
Section: Characteristics Of the School Surroundings Food Intake Andmentioning
confidence: 96%
“…In Scotland, though clustering of all types of food outlets was observed at 400, 800 and 1,200 metre (m) secondary school fringe buffers there was no clear pattern of outlet type clustering (Ellaway et al, 2012). In Germany no food outlet clustering was observed within 750 metres of schools (Buck et al, 2013).…”
mentioning
confidence: 90%